Glubran- 2 Acrylic Glue for Percutaneous Embolization of Intramuscular Vascular Malformations of Lower Limbs: Preliminary Experience - Stillo, Francesco; Ruggiero, Federica; Mattassi, Raul; Amato, Bruno; Compagna, Rita (Journal of Basic & Applied Sciences, 2020)
Aims: Vascular anomalies (VA) represent a heterogeneous and rare group of pathologies. Ethanol is considered the gold standard in endovascular embolization procedures, but its use exposes to the risk of major complications. Glubran-2 is a new glue agent, used mainly for catheter-based cerebral embolization. Our study reported preliminary experiences with a group of 13 patients treated for intramuscular VA of limbs with Glubran-2 solution by venous retrograde percutaneous embolization. Methods: Through an Angiographic CT/MRI we selected 13 adult patients (6 males, 7 females), seven with limb AVMs and six with limb VM, all intramuscular. All patients reported pain and functional limitation as presenting symptoms. Glubran-2 was injected under fluoroscopic guidance through multiple percutaneous punctures, to cover the entire extension of the lesion. Results: In the 6-month follow-up, all patients reported pain reduction, rapid recovery of function, favourable post-operative course and absence of major complications. Angio-RMI control was performed in all patients. It showed Glubran-2 in place and the exclusion of the malformation. Percutaneous retrograde embolization with Glubran-2 permanently excluded muscle malformations from circulation: only one embolization procedure was, in 12 of 13 patients, sufficient for a complete and definitive treatment. Rapid polymerization of Glubran-2 glue, after its injection, cancelled the risk of pulmonary embolisms and skin necrosis. Secondary surgical removal was never necessary to complete treatment of these deep muscle malformations. Conclusions: This study showed that the percutaneous embolization technique with Glubran-2 glue can be considered favorable in the treatment of the VA of the limbs for its easier handling and promising outcome.